2017
DOI: 10.1016/j.firesaf.2017.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive wind tunnel experiments of lofting and downwind transport of non-combusting rod-like model firebrands during firebrand shower scenarios

Abstract: To date, due to difficulties in making measurements during wildfires, much of what is known about firebrand showers and the subsequent fire spotting comes from mathematical modeling of the lofting and downwind transport of firebrands. However, these models lack experimental validation. Hence, the coupled lofting and downwind transport of non-combusting rod-like firebrands is experimentally modeled by releasing them through the velocity field of a large scale boundary layer wind tunnel. Complete trajectories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 35 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…The total number of spot fires was correlated with plume behaviour, fuel characteristics (hazard score, age), and wildfire behaviour (rate of spread, intensity, flame height). There have been several international studies focused on determining firebrand landing distributions based on small-scale laboratory experiments and/or mathematical modelling [19][20][21][22][23][24][25][26][27]. These have generally indicated right-skewed distributions of firebrands (e.g., exponential, Rayleigh, lognormal), but normal or bi-modal distributions have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The total number of spot fires was correlated with plume behaviour, fuel characteristics (hazard score, age), and wildfire behaviour (rate of spread, intensity, flame height). There have been several international studies focused on determining firebrand landing distributions based on small-scale laboratory experiments and/or mathematical modelling [19][20][21][22][23][24][25][26][27]. These have generally indicated right-skewed distributions of firebrands (e.g., exponential, Rayleigh, lognormal), but normal or bi-modal distributions have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Firebrand processes are also affected by winds (Tarifa et al, 1965;Lee and Hellman 1969;Albini 1983;Ellis 2000;Albini et al, 2012;Koo et al, 2012;Suzuki et al, 2013;Tohidi et al, 2015;Suzuki and Manzello, 2017a;Tohidi and Kaye, 2017a;Tohidi and Kaye, 2017b;Fernandez-Pello, 2017;Song et al, 2017;Suzuki and Manzello, 2019;Suzuki and Manzello 2020a;Suzuki and Manzello 2021). Wind influences all aspects of firebrand behavior; firebrand generation from fuels (Suzuki et al, 2013;Tohidi et al, 2015;Suzuki and Manzello, 2019;Suzuki and Manzello 2021), transport distance (Tarifa et al, 1965;Lee and Hellman 1969;Albini 1983;Ellis 2000;Albini et al, 2012;Koo et al, 2012;Tohidi and Kaye, 2017a;Tohidi and Kaye, 2017b;Song et al, 2017), firebrand deposition patterns (Suzuki and Manzello, 2017a), and ignition behavior induced by firebrands (Ganteaume 2009;Manzello, 2014;Suzuki et al, 2015;Suzuki and Manzello, 2017b;Manzello et al, 2017;Wang et al, 2017;Suzuki and Manzello, 2020b). Out of four firebrand behaviors, the firebrand deposition is the least studied to the authors' knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The firebrands released in the wind-tunnel at 9 m/s experienced a mass loss of 20-40% when compared to firebrands released in no wind condition. Tohidi and Kaye (2017b), Tohidi and Kaye (2017a) experimentally and computationally studied the lofting of firebrands in a wind tunnel where in addition to wind, a convective plume was included. They observed that for higher wind speeds, the change in the initial vertical velocity of the convective column did not affect the mean or standard deviation of the heights where the firebrands lofted or the distances they traveled to land.…”
Section: Introductionmentioning
confidence: 99%